2010
DOI: 10.1037/a0020032
|View full text |Cite
|
Sign up to set email alerts
|

Staying well and engaged when demands are high: The role of psychological detachment.

Abstract: The authors of this study examined the relation between job demands and psychological detachment fro m work during off-job time (i.e., mentally switching off) with psychological well-being and work engagement. They hypothesized that high job demands and low levels of psychological detachment predict poor well-being and low work engagement. They proposed that psychological detachment buffers the negati ve impact of high job demands on well-being and work engagement. A longitudinal study ( 12-month time lag) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
471
9
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 496 publications
(511 citation statements)
references
References 83 publications
15
471
9
16
Order By: Relevance
“…Applying the COR theory, this is essentially a loss cycle in terms of energy depletion and failure to restore lost energetic resources which rumination further consumes. Without proper recovery and regain of energy, short-term load reactions accumulate and become more harmful (Meijman & Mulder, 1998;Sonnentag et al, 2010). Thus, our results concur with the notion of Querstret et al (2016) that rumination and indicators of lack of energy may be involved in a cycle whereby one feeds the other.…”
Section: Exhaustion and The Profiles Of Work-related Ruminationsupporting
confidence: 85%
See 2 more Smart Citations
“…Applying the COR theory, this is essentially a loss cycle in terms of energy depletion and failure to restore lost energetic resources which rumination further consumes. Without proper recovery and regain of energy, short-term load reactions accumulate and become more harmful (Meijman & Mulder, 1998;Sonnentag et al, 2010). Thus, our results concur with the notion of Querstret et al (2016) that rumination and indicators of lack of energy may be involved in a cycle whereby one feeds the other.…”
Section: Exhaustion and The Profiles Of Work-related Ruminationsupporting
confidence: 85%
“…This is compatible with the notion of exhaustion resulting from impeded recovery after investment of effort in job demands. As for longitudinal evidence, poor psychological detachment predicted an increase in emotional exhaustion within one year (Sonnentag, Binnewies, & Mojza, 2010). Similarly, sustained cognitive activation in the form of preoccupation with thoughts of work during leisure time predicted clinical burnout across two years while controlling for job demands (Söderström, Jeding, Ekstedt, Perski, & Åkerstedt, 2012).…”
Section: Exhaustion As An Outcome Of Work-related Ruminationmentioning
confidence: 98%
See 1 more Smart Citation
“…Although research on recovering from job stress during non-work time extensively demonstrated the positive effect of disengaging from work on health and well-being (e.g., Sonnentag, Binnewies, & Mojza, 2010), recent studies suggest that the link between detachment from work and performance outcomes, such as employee creativity, may not be that straightforward (e.g., Binnewies, Sonnentag, & Mojza, 2009;De Jonge, Spoor, Sonnentag, Dormann, & Van den Tooren, 2012;Fritz, Yankelevich, Zarubin, & Barger, 2010).…”
Section: Divergent Effects Of Detachment From Work: a Day-level Studymentioning
confidence: 99%
“…Sonnentag, Binnewies, & Mojza, 2010). The uncertainty scale assesses role ambiguity and role conflict: (1) "How often to you get unclear instructions?…”
Section: Role Uncertaintymentioning
confidence: 99%